Warm Compress to Overcome Hyperthermia: A Case Study - Siwi Tri Guno Respati; Murniati; Noor Yunida Triana (Inspirasi Foundation, 2022)
Objective: To find out the description of giving warm compresses to treat hyperthermia in An.M with febrile seizures in the Parikesit room of RST Wijayakusuma. Method: This type of research was qualitative, with a case study design that was described descriptively. In this case study, the subject is An.M with hyperthermia nursing problems in cases of febrile seizures at Wijayakusuma Hospital, Purwokerto. Data collection in the following research was carried out by means of observation, measurement, in-depth interviews or anamnesis (assessment by direct interviews with patients or families), physical examination, and documentation for the same data source. Result: The results obtained after giving compresses for 3 days the patient's body temperature which was originally 38.50C dropped to 370C. Conclusion: It was concluded that hyperthermia can be overcome by giving warm compresses, warm compresses cause the body temperature outside to be warm so that the body will interpret that the outside temperature is quite hot, eventually the body will reduce the temperature control control in the brain so as not to increase the body temperature, with the outside temperature Warmth will make the peripheral blood vessels in the skin widen and experience vasodilation so that the skin pores will open and facilitate heat dissipation, so there will be changes in temperature. This can be seen from the results of the researcher's evaluation that giving warm compresses can have an impact on decreasing body temperature.